327 Evaluation of the Role of pAKT Expression in Epithelial Mesenchymal Transition in Uterine Carcinosarcoma. (11th January 2018) - Boroujeni, Amir Momeni; Yousefi, Elham; Chen, Ning; Gupta, Raavi
Abstract: Objectives: Epithelial-mesenchymal transition (EMT) has been shown to be the underlying mechanism of the morphologic variation of carcinosarcomas. EMT involves loosening of epithelial adhesion structures and transformation of epithelial cells into mesenchymal cells. It is believed that EMT in uterine carcinosarcomas (UCSs) is due to alterations of the AKT-pathway. Increased AKT expression leads to modulation of expression of downstream genes, such as SLUG, leading to cytoskeletal and cell-cell adhesion changes. Loss of E-cadherin expression is the hallmark of EMT. In this study, we investigated the role of AKT in EMT of UCS. Methods: A total of 33 cases of UCS were selected, and survival data were obtained. Immunohistochemical staining with E-cadherin (EP700Y, 1:200 dilution, Roche-Ventana) and pAKT (ab8805, 1:350 dilution, Abcam) was performed. Expression pattern of the antibodies was assessed in the epithelial and mesenchymal components of the tumor. Loss of E-cadherin in the mesenchymal component was considered epithelial mesenchymal transition. Staining of <20% cells was considered negative. Survival data were compared using cox regression to determine the prognostic significance of AKT expression. Results: Of 33 cases, 28 showed loss of E-cadherin expression in mesenchymal component. Fourteen of 28 cases (50%) showed increased expression of pAKT in the mesenchymal component. Three of 28 cases (10.7%) showed positivity of both components, and in 10/28 cases (35.7%), both components were negative for pAKT. One case showed positive pAKT staining in the epithelial component and negative staining in the mesenchymal component. Survival analysis showed no prognostic effect of AKT expression. Conclusion: AKT pathway is the main mechanism of epithelial mesenchymal transition in UCS. Our results show that AKT pathway alterations drive the EMT in 50% of UCS cases. In other cases, alternative pathways such as RHOA/ROCK pathway should be investigated. The mechanism of EMT appears to have no effect on survival.